Long noncoding RNA plasmacytoma variant translocation 1 promotes progression of colorectal cancer by sponging microRNA‐152‐3p and regulating E2F3/MAPK8 signaling. Issue 1 (24th November 2021) - Liu, Xin; Li, Lei; Bai, Jing; Li, Liang; Fan, Jianghe; Fu, Zexian; Liu, Jianxia
Abstract: The purpose of this study was to investigate the pathogenesis of colorectal cancer (CRC) and the effects of the long noncoding RNA plasmacytoma variant translocation 1 (PVT1) on CRC progression. Bioinformatics analysis verified PVT1 expression in tumor and normal tissues. Quantitative PCR and western blotting were used to measure mRNA and protein levels, respectively. The MTT, Transwell, colony formation, and in vivo assays were used to assess the effects of PVT1 on proliferation, migration, and invasion by CRC cells. Both PVT1 and microRNA (miR)‐152‐3p were shown to be colocalized in CRC cells using FISH assay. The target genes of miR‐152‐3p were predicted and verified by bioinformatics analysis, luciferase assay, and RNA pull‐down assay. The ChIP assay revealed that E2F3 binds with the promoter of MAPK8. We found that PVT1 was overexpressed in CRC specimens, and its expression was higher in CRC cells than normal intestinal cells. Overexpression of PVT1 enhanced the proliferation, migration, and invasion of CRC cells, whereas PVT1 knockdown inhibited these processes. MicroRNA‐152‐3p was a target of PVT1, and E2F3 was a target of miR‐152‐3p. Rescue experiments confirmed the interaction between miR‐152‐3p and PVT1 and between miR‐152‐3p and E2F3. Luciferase and ChIP assay results confirmed that E2F3 modulates the transcriptional activation of MAPK8. Long noncoding RNA PVT1 activated E2F3 signaling by sponging miR‐152‐3p. The PVT1/miR‐152‐3p/E2F3/MAPK8 axis promoted CRC progression. Abstract : Plasmacytoma variant translocation 1 (PVT1) activated E2F3 signaling by sponging microRNA (miR)‐152‐3p. The PVT1/miR‐152‐3p/E2F3/MAPK8 axis promoted colorectal cancer progression.